(untitled) (Asian-Australasian Journal of Food Safety and Security, 2020)
The present research work was carried out to evaluate the qualities of borhani prepared by curd using whole milk, skim milk and full cream powder milk. In this purposes, three types of borhani were prepared, these were grouped as; A: Borhani prepared from whole milk curd, B: Borhani prepared from skim milk curd and C: Borhani prepared from full cream powder milk curd. The prepared borhani samples were subjected to organoleptic, chemical and microbiological qualities. After performed physical examination, for sample A it was found that there was no significant difference in color and appearance (17.67±0.33) but there was significant difference (p<0.05) in smell and taste (47.33±0.33), body and consistency (26.33±0.33) and total physical scores (91.33±0.88) of the three borhani samples. Chemical analysis showed that for group A; there were significant differences with others (p<0.01) in contents (%) of fat (2.95±0.33), total solids (TS) (18.15±0.16), acidity (0.80±0.01), pH (4.25±0.02), moisture (81.85±0.16), CHO (10.50±0.93) and (p<0.05) in contents (%) of ash (1.82±0.02), protein (2.88±0.02). The result of chemical parameter showed that borhani prepared from whole milk (sample A) was best among the samples. However, there were no significant differences in coliform count and yeast and mold count but there were significant differences (p<0.01) in total viable count (60.67±2.33). Cost analysis showed that samples B and C was cheap than sample A. It can be concluded that even costly; the nutritive value and the consumer preference of borhani from whole milk was better than the others. Asian Australas. J. Food Saf. Secur. 2020, 4 (2), 58-65